2011
DOI: 10.1124/jpet.111.180364
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Suppression of Prostatic Cancer Cells by Coexpression of BothMurine Double Minute 2Small Interfering RNA and Wild-Typep53Gene In Vitro and In Vivo

Abstract: Our objective was to evaluate cell growth and death effects by inhibiting Murine Double Minute 2 (MDM2) expression in human prostate cancer cells overexpressing the wild-type (WT) p53 gene. Prostate PC-3 tumor cells were transfected with a plasmid containing either mdm2 small interfering (Si-mdm2) or the WT p53 gene (Pp53) alone, or both (Pmp53), using Lipofectamine in vitro and attenuated Salmonella enterica serovar Typhi vaccine strain Ty21a (Salmonella Typhi Ty21a) in vivo. Cell growth, apoptosis, and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Typhimurium, which could selectively target tumors and deliver the therapeutic agents into tumors while reducing the damage to normal tissue [23,33,34]. More recently, these bacteria have been engineered to express numerous genes, including survivin [35], MDM2 [36], Neu3 [37] and STAT3 siRNA [25] against prostate cancer in our laboratory. So this time, we first employed the attenuated S. enterica ser.…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium, which could selectively target tumors and deliver the therapeutic agents into tumors while reducing the damage to normal tissue [23,33,34]. More recently, these bacteria have been engineered to express numerous genes, including survivin [35], MDM2 [36], Neu3 [37] and STAT3 siRNA [25] against prostate cancer in our laboratory. So this time, we first employed the attenuated S. enterica ser.…”
Section: Discussionmentioning
confidence: 99%
“…The transfection reagent used was Lipofectamine 2000 (Invitrogen, CA, USA). Approximately 6 × 10 3 cells per well were transfected with the plasmids with or without DDP for 48 h, then cell viability was determined by (3-(4,5-dimethylthiazolyl-2)-2,5-diphenyltetrazolium bromide (MTT, Sigma-Aldrich) assay following standard protocols as previously described 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Genetically attenuated bacteria such as attenuated Salmonella offers promise as an anticancer vector and has been widely used as a tool to deliver plasmids that express siRNA in vivo 1621 . Our previous studies have demonstrated that a combination of low-dose DDP with gene therapy expressing tumor protein p53 (p53) and mouse double minute 2 homolog (MDM2) siRNA, delivered by attenuated Salmonella enterica serovar Typhi vaccine strain Ty21a ( Salmonella Typhi Ty21a ), synergistically inhibited ovarian cancer and PCa growth without damaging normal tissues 2225 . Here, we tested our hypothesis that knockdown of HIF-1α by siRNA gene therapy delivered by the attenuated Salmonella Typhi Ty21a is a promising strategy to increase the sensitivity of PCa to DDP from the perspective of targeting cancer-specific metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Statistical analysis After washing with PBS, the samples were TUNEL stained according to the manufacturer's instructions (Promega).…”
Section: Tunel Assay and Immunohistochemical Stainingmentioning
confidence: 99%